Mutual transformation through Arts-based Service Learning with First Nations communities: An Australian Case Study - Power, A.; Bennett, Dawn; Bartleet, B. (Indiana State University, 2014)
This paper reports from a national arts-based service-learning project in Australia. Working with pre-service teachers, the paper employs the theoretical framework of sentipensante (sensing/thinking), which has been successfully used in disciplines such as policy, leadership and communication. Participant stories reveal a network of relations that create understanding of shared existence, and these learning experiences emerge as variously threshold, transformative, and/or troublesome. Findings lend support to the value of flexible, critical service learning approaches, particularly in diverse cultural contexts.